Hablemos del derecho a la vida - Hernán Olano García (Ius Humani. Jornal do direito, 2016)
With the objective of highlighting the value of the fundamental right within the fundamental rights, according to the Political Constitution of Colombia (and other constitutions) and, within its line of research in history of the institutions-I, the author makes some reflections on the right to life , Following a deductive methodology, according to the most important aspects that both the doctrine and the jurisprudence have contributed to structure the article in several sections such as: (i) its sacredness, (ii) a right to death?, (iii) the ontological dignity of the Life and (iv) the day of life, which recognizes the protection of this right of every person, as the foundation and end of the whole just social order. The principal conclusion is the sacred and juridical value of human life, endowed with transcendence in the positive ordering by its natural origin.